Melioidosis in Sri Lanka - Corea, Enoka M. (Trop Med Infect Dis, 2018)
Until recently, Sri Lanka was not considered a country with endemic melioidosis. However, an increasing number of cases is being reported. National surveillance for melioidosis was instituted after 2008. A total of 250 culture-positive cases was recorded between 2006 and May 2017. Males predominated (71.6%). The age range was wide (2–92 years) reflecting a ubiquity of exposure. The majority (201/250, 80%) lived in rural areas. All provinces were affected. Case load increased during the two monsoonal periods (67%). There was representation of every population group including farmers (n = 44), housewives (n = 24), school children (n = 10), professionals (n = 5), businesspersons (n = 6), white-collar workers (n = 10) and blue-collar workers (n = 8). Diabetes was the predominant risk factor (n = 163, 65.2%). Clinical presentations included community-acquired sepsis and pneumonia, superficial and deep abscesses, and septic arthritis. Mortality was 20.4% (51/250). A majority (n = 212) of isolates belonged to the YLF (Yersinia-like fimbrial) clade but 38 were BTFC (B. thailandensis-like flagellum and chemotaxis). A total of 108 isolates was genotyped and 46 sequence types (STs) were identified, 40 being novel. It is clear that melioidosis is endemic in Sri Lanka with a wide geographic and demographic distribution. There is an urgent need to extend surveillance of melioidosis to under-resourced parts of the country and to populations at high risk.